FUTURE OF CREATIVITY: HUMAN COGNITION AND ARTIFICIAL IMAGINATION - Adoma, Floradel; Mateo, Maylane; Cabutaje, Rolando; Viscarra, Edward; Danao, Jennifer Cabanting; Singh, Arpita; Damodaran B. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Abstract Creativity is considered to be one of the hallmarks of human cognition, and it is based on the complex processes in the neural and cultural as well as in the experience aspect. However, recent developments in the area of artificial intelligence have presented systems that can create images, music, text, and design products that contradict the classic separations between human creativity and machine production. The paper will discuss the future of creativity by looking at it through the prism of human cognition and artificial imagination and provide an integrative approach to creativity that places creative intelligence on a human machine spectrum, instead of it being a two-pole conceptualization. Based on classical creativity theories, such as Gestalt, psychoanalytic, and cognitive theories, the study describes the emergence of divergent and convergent thinking based on neural networks developed as a result of cultural influences, embodiment, and lived experience. The restrictions and biases of the data-based systems are specifically addressed and the essence of the differences in biological cognition and algorithmic creation is pointed out. The paper also examines human-AI co-creativity models, whereby creativity is created by collaborative processes, inter-retrospective processes, and collective agency between human will and machine production. In addition to technical issues, the study is operating within the ethical, philosophical, and social concerns of authorship, originality, ownership, and cultural influence of creative AI. Lastly, it also describes future directions, which are neuro-symbolic systems, affective and embodied AI, and personalized creative agents that respond to individual cognitive styles. The paper is a synthesis of insights on cognitive science, artificial intelligence, and creative practice, which is why it provides a conceptual framework to understand how creativity can be developed in a world of more intelligent machines.